Morphometric parameters of pelvis in perinatal period of human ontogenesis. - Vasylchyshyna А. V.; Khmara Т. V.; Ryznychuk М. О. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Defects of the musculoskeletal system occupy the second place in the structure of congenital malformations of newborns, and the first place in infants of the Chernivtsi region. Objective. Clarification of morphometric parameters of pelvic external dimensions, pelvic inlet and outlet sizes and the size of its cavity in fetuses of 6-10 months of gestational age and in newborns. Methods. The study was conducted on 82 specimens of 6-10 months fetuses of 186,0-375,0 mm of parietal-coccygeal length and on 10 infants with no outer signs of human anatomical abnormalities or congenital malformations. Results. In fetuses of 6-10 months and in newborns we examined the external dimensions of the pelvis, which were significantly increase – interspinal distance was increased in 3,0 times. External conjugate was significantly increased over the period of observation – in 2,7 times. During the studied period of ontogenesis all inlet pelvic sizes were significantly increased, anatomic conjugate - on 2,3 mm, oblique conjugate – on 2,2 mm, transverse diameter - on 2,4 mm and oblique diameter - on 1,9 mm. The dimensions of the pelvic cavity: middle conjugate and transverse diameter of the pelvic cavity increased during the investigated period on 2,2 mm and 3,4 mm respectively. The dimensions of the pelvic outlet: straight conjugate and transverse size of pelvic outlet also were increased significantly on 2,2 mm and on 2,7 mm respectively. Conclusion. All morphometric parameters of the pelvis in the studied period of human ontogenesis were significantly increased. The most intensive growth was observed in the following structures: distance interspinalis - 3,0-fold increase and transverse diameter of the pelvic cavity - 3,4-fold increase.